2012
DOI: 10.1111/j.1440-1843.2012.02184.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the frequency of CD4+CD25+CD127− T‐cells in patients with pulmonary tuberculosis and diabetes mellitus

Abstract: In patients with pulmonary tuberculosis and DM, the imbalance between Treg and effector T-cells at pathological sites may be associated with weakened immunity and clinical manifestations of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
0
15
1
3
Order By: Relevance
“…TB-DM cases also have a higher frequency of single- and double-cytokine producing CD4+ Th1 cells in response to Mtb antigens (for IFN-γ, TNF-α or IL-2) (37). These hyper-active responses in peripheral blood contrast with the results from few studies conducted at the site of infection (in bronchoalveolar lavage) where TB-DM patients appear to have reduced activation of immunity; one reported a lower proportion of activated alveolar macrophages (70), and another higher anti-inflammatory (IL-10) and lower pro-inflammatory (IFN-γ) cytokines (71). The impact of the host compartment (peripheral blood versus lung) requires further study.…”
Section: Biological Basis For the Association Between Tb And Dmcontrasting
confidence: 61%
“…TB-DM cases also have a higher frequency of single- and double-cytokine producing CD4+ Th1 cells in response to Mtb antigens (for IFN-γ, TNF-α or IL-2) (37). These hyper-active responses in peripheral blood contrast with the results from few studies conducted at the site of infection (in bronchoalveolar lavage) where TB-DM patients appear to have reduced activation of immunity; one reported a lower proportion of activated alveolar macrophages (70), and another higher anti-inflammatory (IL-10) and lower pro-inflammatory (IFN-γ) cytokines (71). The impact of the host compartment (peripheral blood versus lung) requires further study.…”
Section: Biological Basis For the Association Between Tb And Dmcontrasting
confidence: 61%
“…TB-DM cases also have a higher frequency of single- and double-cytokine producing CD4+ Th1 cells in response to Mtb antigens (for IFN-γ, TNF-α or IL-2) [24]. These hyper-active responses in peripheral blood contrast with the results from few studies conducted at the site of infection (in bronchoalveolar lavage) where TB-DM patients appear to have reduced activation of immunity; one reported a lower proportion of activated alveolar macrophages [26], and another higher IL-10 (which is anti-inflammatory) and lower IFN-γ[27]. The impact of the host compartment (peripheral blood versus lung) requires further study.…”
Section: Dysfunctional Innate and Adaptive Immunity To Mtb In Dm Pmentioning
confidence: 99%
“…20 In the broncho alveolar lavage of TB-DM patients, Sun et al also found higher baseline IL-10, but lower IFN-γ suggesting the lung compartment may have a biased Th2 response in DM. 55 …”
Section: Impact Of Dm On the Natural History Of Tbmentioning
confidence: 99%